Information and communication technology in higher music education: systematic review - Yangyang Wang; Aidah Abdul Karim; Intan Farahana Kamsin (International Journal of Evaluation and Research in Education (IJERE), 2026)
Technological advances have facilitated the integration of information and communication technology (ICT) into higher music education over the past decade. However, existing literature remains fragmented and lacks an integrated understandingof this field. This study addresses four research questions concerning developmental trends, types of ICT use and their characteristics, advantages, and challenges of ICT integration in higher music education. Based on 40 articles retrieved from EBSCO, Scopus, and Web of Science (WoS), this review analyses ICT use in higher music education. The findings show that the reviewed articles are unevenly distributed geographically, with a substantial proportion originating from China. Quantitative research designs dominated the reviewed articles. Thematic analysis identified four primary categories of ICT use: network-based and distance learning technologies, digital platforms and tools, artificial intelligence (AI)-powered educational technologies, and immersive and sensor-based ICT applications. ICT can enhance teaching quality, student motivation, personalized learning, flexibility, instructional innovation, and interdisciplinary integration, while challenges include limited emotional interaction, technical barriers, unequal resource allocation, privacy concerns, and ethical risks. Drawing on the technology acceptance model (TAM) and technological pedagogical content knowledge (TPACK) framework, this study proposes an integrative framework to guide teachers and institutions in designing pedagogically meaningful, technically feasible, and context-sensitive ICT-enhanced music education practices.